2004
DOI: 10.1002/cyto.b.20039
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐B27 typing: Evaluation of an allele‐specific PCR melting assay and two flow cytometric antigen assays

Abstract: Background: Human leukocyte antigen B27 (HLA-B27) is a major histocompatibility complex class 1 molecule that is strongly associated with the disease ankylosing spondylitis. Testing for HLA-B27 is of diagnostic value because 90% of patients with ankylosing spondylitis have the B27 antigen. Two commonly used HLA-B27 flow cytometric assays are commercially available.Methods: An allele-specific polymerase chain reaction (PCR) melting assay for HLA-B27 was compared with two available antigen assays on 371 clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 14 publications
2
17
0
2
Order By: Relevance
“…Nevertheless, when using the GS145.2 antibody assay, a follow-up test should be conducted with an FD705 antibody assay in a specific critical range of the MFI. This can produce a sensitivity of 98.8% and a specificity of 97.6% [25].…”
Section: Hla-b27mentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, when using the GS145.2 antibody assay, a follow-up test should be conducted with an FD705 antibody assay in a specific critical range of the MFI. This can produce a sensitivity of 98.8% and a specificity of 97.6% [25].…”
Section: Hla-b27mentioning
confidence: 97%
“…Compared to the gold standard of DNA sequencing, a sensitivity of 99.6% and a specificity of 100% is reached, depending on the primer mix employed [25]. But the choice of primer can also create limitations, because not all subtypes are captured all the time: When using the PCR protocol according to Olerup, the subtypes B*27:12, B*27:16, B*27:18 and B*27:23 are not amplified, and using the PCR according to Dominguez, this is true of the subtypes B*27:07, B*27:14, B*27:19 and B*27:21 [26].…”
Section: Hla-b27mentioning
confidence: 99%
“…En su esencia la citometría de flujo representa un proceso técnico importante debido en gran medida a su carácter multiparamétrico en la detección de una o más características físicas y/o químicas de la superficie celular analizando un alto número de partículas en corto tiempo (3). La técnica de biología molecular (PCR) es considerada como el estándar técnico de oro para la determinación de HLA-B27, tal y como se reporta en estudios como el de Bonnaud (2), Nicknam et al (7), o el de Seipp et al (6), quienes mencionan que la técnica para la determinación de HLA-B27 que tiene una mejor sensibilidad y especificidad frente a los demás ensayos es la PCR (6), los resultados del presente estudio nos demuestran una muy buena utilidad de la CMFd fundamentada en una mejor sensibilidad, objetividad, rapidez y versatilidad analítica de tamizaje frente al estudio celular. Al comparar la CMFd con la PCR-SSP la concordancia obtenida muestra que los resultados adquiridos por la técnica de CMFd presentan una confiabilidad alta (94,5%) y menos tiempo para su procesamiento.…”
Section: Concordancia Entre Técnicasunclassified
“…In particular, the PCR-SSP technique relies on the recognition of HLA-B*27 specific DNA sequences, and thus is an ideal test for HLA-B*27. Previous results have concluded that the outcomes obtained by PCR-SSP are more accurate compared with the conventional serological approach (15).…”
Section: Introductionmentioning
confidence: 97%
“…Major drawbacks of MLCT include the requirement for viable cells, cross-reactivity of antigens, the requirement for a single individual to provide consistent and accurate results, and unavailability of B*27 specific antisera covering all HLA-B*27 alleles (14). Flow cytometry is often used due to its efficiency as an alternative HLA-B*27 detection technique; however, cross-reactivity with other HLA-B molecules including B7 is a major limitation (15,16). Furthermore, it requires expensive reagents, complex equipment and specifically trained personnel.…”
Section: Introductionmentioning
confidence: 99%